Plasma antioxidants and glutamine supplementation in HIV - Burini, Roberto Carlos [UNESP]; Borges-Santos, Maria Dorotéia [UNESP]; Moreto, Fernando [UNESP]; Yu, Yong-Ming (Springer Nature, 2015)
HIV+ patients present higher plasma levels of pro-oxidant and lower antioxidant markers irrespective of their nutritional status and the presence of HAART [1]. The presence of HAART showed some beneficial effects on β-carotene plasma levels but not on the other antioxidant markers [2]. Among those were glutathione (GSH) and its precursors [3]. GSH (l-y-glutamyl-l-cysteinyl-glycine) is the major intracellular hydro-soluble antioxidant agent representing important functions in biochemical processes and cell control, specially the antioxidant and immune defenses [4]. Plasma GSH can also be used as forms of cysteine storage and transport, with consequences for the regulation of signal transduction pathways and gene transcription [5].
Keywords: Glutathione antioxidant metabolism; HIV+; Oral glutamine supplementation; Sulfured-amino acids metabolism